Access to health-care policies for refugees and asylum-seekers. Issue 1 (12th February 2020) - El-Gamal, Salma; Hanefeld, Johanna
Abstract : Purpose: The influx of refugees and asylum-seekers over the past decade into the European Union creates challenges to the health systems of receiving countries in the preparedness and requisite adjustments to policy addressing the new needs of the migrant population. This study aims to examine and compare policies for access to health care and the related health outcomes for refugees and asylum-seekers settling both in the UK and Germany as host countries. Design/methodology/approach: The paper conducted a scoping review of academic databases and grey literature for studies within the period 2010-2017, seeking to identify evidence from current policies and service provision for refugees and asylum-seekers in Germany and the UK, distilling the best practice and clarifying gaps in knowledge, to determine implications for policy. Findings: Analysis reveals that legal entitlements for refugees and asylum-seekers allow access to primary and secondary health care free of charge in the UK versus a more restrictive policy of access limited to acute and emergency care during the first 15 months of resettlements in Germany. In both countries, many factors hinder the access of this group to normal health care from legal status, procedural hurdles and lingual and cultural barriers. Refugees and asylum-seeker populations were reported with poor general health condition, lower rates of utilization of health services and noticeable reliance on non-governmental organizations. Originality/value: This paper helps to fulfill the need for an extensive research required to help decision makers in host countries to adjust health systems towards reducing health disparities and inequalities among refugees and asylum-seekers.